Wpływ poziomu zakłóceń losowych na możliwość identyfikacji modeli ARIMA - Nazarko, Joanicjusz; Rybaczuk, Mikołaj; Jurczuk, Arkadiusz (Influence of Random Noise on An Identification of ARIMA Models, 2005)
The main problem of time series modelling with ARIMA models is to identify class (autoregression, moving average, autoregression and moving average) and their order. The basis for the identifying is an analysis of plot of autocorrelation (AC) and partial correlation functions (PAC). The paper presents results of simulation research on influence of white noise presence and its variance level on identification of basic ARIMA models. The effect of noise variance level on a quality of estimation of ARIMA models has been also presented in the paper. It has been considered that possibility of correct identification and estimation strongly depends on presence and variance of a random noise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 238-247